Consumer Preferences For Imitation Jersey Shirts: A Conjoint Analysis - Sya'dulloh Efendy; Siti Zuhroh (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2020)
Abstract This research, which was conducted in 2019, aims to determine the consumer preferences of the Persebaya imitation T-shirt jersey in Jombang district. The method used in this research is a descriptive exploratory method with a quantitative approach. The population in this study were unknown Persebaya imitation jersey consumers, so the sampling technique was determined by non probably sampling by taking 100 respondents. The data used are primary and processed using conjoint analysis. The results showed that from all respondents the combination of Persebaya soccer jersey products that became the consumer's preference was the jersey price <Rp. 100,000, dark green jersey color, no collared jersey shape, and a jersey image (there is a name, jersey number, and sponsor). Thus it can be concluded that in choosing the Persebaya T-Shirt jersey, the most important attributes that influence consumer purchasing decisions are: 1) color, 2) shape, 3) image, and 4) price.